Dual laser excitation of a photochromic system: application to DODCI - Duchowicz, Ricardo (1992)
A technique based on a combination of pump-and-probe fluorescence and absorption detection was developed in order to obtain the emission parameters of the pholoisomeric (P) species of dyes with noncompletely overlapped absorption spectra of P and the starting species (N ). Near total population transfer to the ground state of P was achieved using a continuous wave high fluence pump laser. A pulsed laser probed this population in its absorption region in such a way that the pulsed emission corresponded to fluorescence from P. Absorption measurements allowed us to follow the P population and to establish its relationship with pump fluence and wavelength. The direct monitoring of the P concentration increased the accuracy of the previously reported values for several photophysical parameters. Temperature dependent fluorescence quantum yield and lifetime, emission spectrum, and Arrhenius parameters of the nonradiative decay processes of P from 3,3' diethyloxa dicarbocyanine iodide (DODCI) are given. The mechanism for the direct transformation between N and P through the singlet excited states of DODCI is reevaluated.